Usability of “iCollege” Learning Management System in University Environment - K.H. Wijesinghe; Dilshan.U.K.T; Dilshan.K.B.G.L; Tharupathi.M.A.U; D. I. De Silva; R.R.P. De Zoysa (International Journal of Engineering and Management Research, 2022)
In recent years, there has been an increasing demand in integrating new technologies into educational procedures. The Learning Management System (LMS), a web-based educational technology, helps teachers meet their pedagogical objectives, organize course materials, and support students. Learning Management Software (LMS) has been implemented in many universities across the world to assist link faculty and students outside of the classroom setting. It is a digital environment that allows the efficient distribution of academic materials, Easy access to information, instant access to up-to-date content, maintain a library virtually and enhanced communication through a single location. The main scope of developing this Learning Management System is to resolve above-described features and address many issues in the Academic process and content deliverables. The software solution has been implemented by addressing each requirement of administrators, Students, and Lecturers following each phase of the software life cycle in order to provide real time operations and advanced functions for the web based LMS system